Neuroligin Plays a Role in Ethanol-Induced Disruption of Memory and Corresponding Modulation of Glutamate Receptor Expression - Rose, Jacqueline K.; Butterfield, Michael; Liang, Joseph; Parvand, Mahraz; Lin, Conny H. S.; Rankin, Catharine H. (Frontiers in Behavioral Neuroscience, 2022)
Exposure to alcohol causes deficits in long-term memory formation across species. Using a long-term habituation memory assay in Caenorhabditis elegans, the effects of ethanol on long-term memory (> 24 hours) for habituation were investigated. An impairment in long-term memory was observed when animals were trained in the presence of ethanol. Cues of internal state or training context during testing did not restore memory. Ethanol exposure during training also interfered with the downregulation of AMPA/KA-type glutamate receptor subunit (GLR-1) expression previously associated with long-term memory for habituation in C. elegans. Interestingly, ethanol exposure alone had the opposite effect, increasing GLR-1::GFP expression levels. Worms with a mutation in the C. elegans ortholog of vertebrate neuroligins (nlg-1) were resistant to the effects of ethanol on memory, as they displayed both GLR-1::GFP downregulation and long-term memory for habituation after training in the presence of ethanol. These findings provide insights into the molecular mechanisms through which alcohol consumption impacts memory.